COMMON SIZE ANALYSIS OF THE FINANCIAL STRUCTURE OF BANK SYARIAH INDONESIA AND MALAYSIA YEAR 2022–2023 - Leepum, Abad (Universitas Muhammadiyah Surabaya, 2025)
The growth of the Sharia finance industry in Southeast Asia, particularly in Indonesia and Malaysia, demonstrates an intriguing dynamic in the management of asset and liability structures of Sharia banks. This study focuses on how the proportional differences in financial composition reflect managerial strategies, operational efficiency, and the maturity levels of the Sharia banking systems in both countries. The approach employed is quantitative-descriptive, utilizing common size analysis on the financial reports of Bank Syariah Indonesia (BSI) and Maybank Islamic Berhad for the period 2022–2023. Data was obtained from official annual reports and processed using Microsoft Excel. The results show that BSI allocates over 65% of its total assets to domestic financing, indicating a strong focus on real sector intermediation. In contrast, Maybank Islamic exhibits broader diversification, with Sharia financial instruments accounting for 15–18%. On the liability side, BSI relies on third-party funds up to 75%.